2013
DOI: 10.1245/s10434-013-3083-6
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous Angiosarcoma: A Single-Institution Experience

Abstract: Background Cutaneous angiosarcoma (CAS) is a rare, aggressive vascular sarcoma with a poor prognosis, historically associated with 5-year overall survival (OS) rates between 10 and 30 %. Methods This is a single-institution retrospective review of patients treated for CAS from 1999–2011. Demographics, primary tumor characteristics, treatment, and outcomes were analyzed. Results A total of 88 patients were identified (median age 70 years and 57 % female). Median tumor size was 3 cm. Median follow-up was 22 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
56
1
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(63 citation statements)
references
References 21 publications
(23 reference statements)
5
56
1
1
Order By: Relevance
“…Contrary to previously published single-institutional reports and review studies, [3][4][5] we did not find any evidence to suggest that RT or CT had any independent survival benefit. We have also found surgery to be associated with significant survival benefit.…”
contrasting
confidence: 99%
See 1 more Smart Citation
“…Contrary to previously published single-institutional reports and review studies, [3][4][5] we did not find any evidence to suggest that RT or CT had any independent survival benefit. We have also found surgery to be associated with significant survival benefit.…”
contrasting
confidence: 99%
“…1,3 Due to low incidence rates, the clinical outcome data have been limited to case reports and single institution studies, with a lack of direct comparison between various treatment modalities: surgery, RT and chemotherapy (CT). 4,5 In this study, we aimed to investigate the impact of undergoing different therapeutic approaches on long-term overall survival (OS) using cross-institutional data. The National Cancer Database (NCDB), a joint project of the American Cancer Society (ACS) and the Commission on Cancer (CoC) that currently captures over 70% of all newly diagnosed malignancies in the United States yearly, was queried for patients diagnosed with cutaneous angiosarcoma from 2004 to 2012.…”
mentioning
confidence: 99%
“…[5][6][7] Patients' prognosis, however, remains poor with a 5-y survival of approximately 10% to 20% due to the eventual formation of distant metastases. [8][9][10] The development of more effective treatments is therefore required, and immunotherapy could be a therapeutic option. Fujii et al reported that antitumor immunity with CD8 C T cells in tumor-infiltrating lymphocytes (TILs) is important to prevent the progression of CAS.…”
Section: Introductionmentioning
confidence: 99%
“…The 5-year overall survival (OS) has been variously reported as 24% to 35%. 1,2 When radiotherapy (RT) is given as the main treatment, median survival is only 8 months. 3 Almost half (43%) of angiosarcomas originate from the skin of the head and neck.…”
Section: Introductionmentioning
confidence: 99%
“…3 Almost half (43%) of angiosarcomas originate from the skin of the head and neck. 1,2 Compared with truncal and extremity angiosarcoma, the prognosis of cutaneous angiosarcoma (CAS) of the head and neck is even worse. Perez et al 2 indicated a greater need for flap or graft reconstruction after tumour extirpation for head and neck CAS (HNCAS), a ORIGINAL ARTICLE was 7.5 months.…”
Section: Introductionmentioning
confidence: 99%